Comparison of Two Risk Models in Predicting the Incidence of Contrast‐Induced Nephropathy after Percutaneous Coronary Intervention. (4th July 2016) - Araujo, Gustavo N.; Wainstein, Marco V.; McCabe, James M.; Huang, Pei‐Hsiu; Govindarajulu, Usha S.; Resnic, Frederic S.
Abstract : Objectives: We sought to compare 2 contrast‐induced nephropathy (CIN) risk prediction models in a validation cohort using a consensus definition. Background: Contrast‐induced nephropathy (CIN) is independently associated with mortality following percutaneous coronary intervention (PCI). Multiple prediction models for the development of CIN have been published using heterogeneous outcome definitions. Methods: We analyzed 5, 540 patients who underwent PCI from January 2005 to June 2012 at a single academic medical center. The primary outcome was development of CIN, defined as an increase in serum creatinine of ≥0.5 mg/dl or a relative increase of ≥25% from baseline. Receiver operator characteristic (ROC) curves were used to evaluate the discriminatory power of Mehran and WBH prediction models. Results: The mean age of our cohort was 68 ± 12 years. The mean baseline creatinine was 1.2 ± 0.53 mg/dl (eGFR 73 ± 27 ml/min). The mean contrast volume used was 212 ± 92 ml. CIN occurred in 436 patients (7.9%). The Mehran risk score demonstrated better discrimination than the William Beaumont Hospital (WBH) risk score to predict the occurrence of CIN (c statistic: 0.82 vs. 0.73, respectively). Mortality at 30 days was approximately 8 times higher among patients with CIN as compared to those without (14.7% vs. 1.8% P < 0.01). Conclusions: In an independent validation cohort, the Mehran risk model demonstrates greater discriminatory power than the WBH model in predicting the incidence of CIN. Mortality was significantly higher in patients who developed CIN after PCI.